2018
DOI: 10.1111/ajag.12558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plantar sensitivity on balance and mobility in community‐dwelling older adults: A Turkish study

Abstract: This study revealed that plantar tactile sensory was not associated with balance and mobility functions in older adults. This result may be related to the protection of other sensory systems supporting the maintenance of balance and mobility functions in physically active community-dwelling older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 28 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…In contrast to proprioception, no relation was detected between cutaneous sensitivity and dynamic balance control. Our outcomes agreed with one study, which indicated that cutaneous sensitivity was not correlated with BBS, 23 but disagreed with another, which argued that cutaneous sensitivity in the great toe has some relationship to dynamic balance control. 24 Unlike ours, however, the latter study used only one monofilament (5.07 g, 10 g) to get a cutaneous tactile score.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In contrast to proprioception, no relation was detected between cutaneous sensitivity and dynamic balance control. Our outcomes agreed with one study, which indicated that cutaneous sensitivity was not correlated with BBS, 23 but disagreed with another, which argued that cutaneous sensitivity in the great toe has some relationship to dynamic balance control. 24 Unlike ours, however, the latter study used only one monofilament (5.07 g, 10 g) to get a cutaneous tactile score.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies that supported our observations report that cutaneous sensitivity is not related to dynamic balance control or falls and point out that the loss of sensitivity may be compensated by other sensorial systems. 23 , 61 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the true influence of foot sensitivity on balance is not known. For example, plantar tactile sensitivity was not associated with balance and mobility function in one study with older adults . Additionally, it is relevant to investigate the influence of overweight or obesity on balance, given the association of impaired plantar sensitivity and increased postural sway among the obese .…”
Section: Introductionmentioning
confidence: 99%